Morphometric Study of Distal End of Human Dry Radii - Kadel, Muna; Thapa, Trilok Pati (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Radius is the lateral bone of forearm. Important parameters of its distal end include angle of radial inclination, palmar tilt, and length of radial styloid process. Morphometry of the distal end of radius is important in various clinical orthopaedic procedures such as reduction of distal radius fractures, design of distal radius prosthesis, and kinematics of the wrist joint. The aim of this study is to determine the angle of radial inclination, palmar tilt, length of styloid process, oblique width, transverse and anteroposterior diameter of distal end of human dry radii in Nepalese population. Methods: This is a descriptive cross-sectional study conducted in the dissection hall of Department of Human Anatomy, Nepalese Army Institute of Health Sciences, Sanobhyrang, Kathmandu, Nepal from October 2019 to November 2019 after obtaining ethical approval. Total 76 human dry radii were included in the study by convenience sampling method. Angle of radial inclination, palmar tilt, length of styloid process, oblique width, transverse and anteroposterior diameter of distal end of human dry radii were studied. Data was collected and analysed by SPSS version 24. Results: Mean length of styloid process was 1.09 cm. Mean anteroposterior and transverse diameter of distal end of radius was 1.88 cm and 2.85 cm respectively. Mean oblique width of distal radius was 2.82 cm. The mean palmar tilt and angle of inclination of radius were 9.72 and 23.62 degree respectively. Conclusions: This study provides the reference data for the anatomical alignment while treating the injuries of the distal end of radius in Nepalese population.